Estimating tropical rain attenuation on the Earth-satellite path using radar data - Badron, Khairayu; Ismail, Ahmad Fadzil; Ismail , Maszlan (Taylor and Francis Group, 2015)
Radar-return echoes, known as ‘reflectivity’, are exploited in the course of estimating rain attenuation along a slant path. Relevant radar gates or ‘range bins’ are identified to correlate a specific satellite path. The reflectivity value of each range bin is converted to rainfall rate using established radar reflectivity values – rainfall rates, (Z–R relation). Specific attenuation is then derived for all associated range bins. The attenuation for each bin is the product of specific attenuation and its effective path length. The summation of attenuation endured by all range bins is inferred as the attenuation along the slant path. In this study, an X-band slant path rain attenuation was estimated using 2.85 GHz (S-band) Terminal Doppler Weather Radar (TDWR) data. A technique to estimate rain attenuation by exploitation of radar information is elaborated in this article. Comparisons between the radar-derived attenuation estimations and actual satellite signal measurements are also presented. The findings were verified by comparing the generated values to the directly measured rain attenuation from the Razak satellite (RazakSAT). Radar reflectivity data were obtained from Kuala Lumpur International Airport (KLIA) radar station operated by the Malaysian Meteorology Department (MMD). Preliminary findings using the most recent Z–R relation (i.e. the generated radar-derived rain attenuation estimations) appear to show lower values than the actual measurements.